Stand growth and carbon stocks of community-based mangrove rehabilitation in Singkawang City, West Kalimantan, Indonesia - DWI ASTIANI; EMI ROSLINDA; TRI WIDIASTUTI; HANNA ARTUTI EKAMAWANTI; WIWIK EKYASTUTI; WAHYU DWIANTO; FARIH ALFIKRI; EUFEMIA Y. NGIDU (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Astiani D, Roslinda E, Widiastuti T, Ekamawanti HA, Ekyastuti W, Dwianto W, Alfikri F, Ngidu EY. 2024. Stand growth and carbon stocks of community-based mangrove rehabilitation in Singkawang City, West Kalimantan, Indonesia. Biodiversitas 25: 2799-2805. The ability of tropical mangrove ecosystems to store carbon in the form of biomass is well-founded. The mangrove forest in Setapuk Besar Village, Singkawang City, West Kalimantan Province, Indonesia has been managed by community members in response to the development of alluvial sediment land in recent years. The community's efforts in Setapuk Besar Village to rehabilitate and manage mangrove forests illustrate how essential mangrove forests are to the local ecology and should be applauded for their success. This study aims to investigate the growth and development, carbon stored and sequestered in mangrove forests planted by community in Setapuk Besar between 2015 and 2020. Field survey was conducted from July to November 2022 by mapping the sediment land that had expanded since 2015 and continued with the measurement of density and diameter of mangrove stands that were systematically planted in each planting year using sampling plot method. In addition, site factors such as pH, carbon content, nitrogen, phosphorus, CEC, and soil solution salinity were investigated. Our findings indicate that due to alluvial sedimentation, the coastline in Setapuk village is expanding by 3.3 to 4.6 ha annually, accumulating 24 ha throughout a six-year period. The mangroves planted in 2015-2016 are now thriving on the new land. The six-year-old trees diameter achieved an average of 6.80±0.13 cm, averaged 5.1 m in height, and increased from 0.45 to 2.2 cm in diameter. The total biomass (above and below-ground) of plants aged 4, 5 and 6 years was 250, 303 and 430 tons ha-1, with a potential to absorb carbon of 28-33 tons ha-1 year-1, correspondingly. Given that this mangrove area plays a crucial role in CO2 capture in nature and has a relatively high ability to absorb and store carbon, conservation efforts and best practices are necessary for this forest.